Purification and characterization of a processing protease from rat liver mitochondria. - Ou, W J (1989)
A processing protease has been purified from the matrix fraction of rat liver mitochondria. The purified protease contained two protein subunits of 55 kd (P-55) and 52 kd (P-52) as determined by SDS-PAGE. The processing protease was estimated to be 105 kd in gel filtration, indicating that the two protein subunits form a heterodimeric complex. At high ionic conditions, the two subunits dissociated. The purified processing protease cleaved several mitochondrial protein precursors destined to different mitochondrial compartments, including adrenodoxin, malate dehydrogenase, P-450(SCC) and P-450(11 beta), but the processing efficiencies were different each other. The endoprotease nature of the processing protease was confirmed with the purified enzyme using adrenodoxin precursor as the substrate; both the mature form and the extension peptide were detected after the processing. The processing activity of the protease was inhibited by metal chelators, and reactivated by Mn2+, indicating that the protease is a metalloprotease.